PENERAPAN AKSARA ARAB PEGON DALAM KALIGRAFI BRANDING - Tasri Jatnika (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Branding Calligraphy is a course derived from an understanding of Paramadina University's values: Islamic, Indonesian, and modern. This course is not widely known, and its values have not been widely communicated to the public. This study describes the background to its existence, the creative process, and its application to various forms of everyday functional objects. This study is a report using qualitative descriptive observation methods on student work and deepening students' understanding of Paramadina's values through responses through interviews and open-ended questions and answers. Student attention and enthusiasm were very positive, and developing this course to gain public appreciation is a future challenge. Keywords: Calligraphy, Handwriting, Students, Indonesianness, Islam, Modernity Abstrak: Kaligrafi Branding adalah sebuah mata kuliah yang dihasilkan dari pemahaman akan nilai nilai Universitas Paramadina yaitu nilai nilai Ke Islaman, Ke Indonesiaan dan Ke Moderenan. Kuliah ini belum banyak diketahui dan nilai-nilainya pun belum disuarkan dengan kuat kepada khalayak. Penelitian ini memaparkan latar belakang dari keberadaannya, proses berkarya dan aplikasinya pada ragam bentuk benda fungsional harian. Penelitian ini berupa laporan dengan metode observasi deskriptif kualitatif pada karya mahasiswa dan pendalaman pemahaman mahasiswa pada nilai-nilai Paramadina dengan respon lewat sejenis wawancara dan tanya jawab terbuka. Atensi dan antusiasme mahasiswa sangat baik dan pengembangan kuliah ini untuk mendapatkan apresiasi masyarakat merupakan tantangan masa hadapan. Kata Kunci: Kaligrafi, Khat, Mahasiswa, Keindonesiaan, Keislaman, Kemoderenan